The Off-Label Use of Antineoplastics in Oncology Is Limited But Has Notable Scientific Support in a University Hospital Setting - Herrero Fernandez, Marta; Molina Villaverde, Raquel; Arroyo Yustos, Monica; Navarro Expósito, Fatima; Lopez Gonzalez, Jose Luis; Luque Infantes, Maria Rosario; Alvarez-Mon Soto, Melchor (Frontiers in Pharmacology, 2019)
Purpose: The off-label (OL) use of antineoplastic drugs for the treatment of various types of tumors in patients of different disease stages is becoming a common occurrence. The objective of this study was to analyze these patterns by quantification and characterization of the OL use of antineoplastic drugs and their level of scientific evidence in a medium-high complexity Spanish general university hospital. Method: All oncology patients who underwent OL treatment with one or several antineoplastics during the 10 years from 2002 to 2012 were retrospectively selected. The use of these drugs was considered OL if they were used for indications, stages, lines of treatment or chemotherapy schemes not reflected in the summary of product characteristics (SmPC) published by the European Medicines Agency (EMA) at the time of prescription. To calculate the prevalence of patients who received 1 or more OL treatments during the study period, all patients were selected who, with the diagnoses included in the study, had received chemotherapy using the minimum set of basic data (MBDS) and the program Farmatools® (Dominion®) that records all patients receiving chemotherapy. Results: In total, 684 patients and 866 OL treatments were included. The prevalence of patients undergoing OL treatment with antineoplastics was 6%. OL treatments were used mainly for breast, gynecological, lung and gastric tumors. The most often used antineoplastic was paclitaxel, followed by gemcitabine, carboplatin, vinorelbine and capecitabine, which were used mainly in monotherapy and with palliative intent. A total of 56.1% of the OL schemes used had a level of evidence of 2A according to the National Comprehensive Cancer Network (NCCN), and 55.3% had a level of evidence of 2B according to Micromedex®. Conclusion: The OL use of antineoplastics in oncology patients is limited; their use is mainly focused in a small group of tumors and at advanced stages of disease. OL use of antineoplastics occurs under palliative therapeutic strategies with a limited number of drugs, preferably off-patent drugs. In addition, these OL treatments have high levels of clinical evidence.